Plasticity in mental health: A network theory. (July 2022) - Branchi, Igor
Abstract: Plasticity is the ability to modify brain and behavior, ultimately promoting an amplification of the impact of the context on the individual's mental health. Thus, plasticity is not beneficial per se but its value depends on contextual factors, such as the quality of the living environment. High plasticity is beneficial in a favorable environment, but can be detrimental in adverse conditions, while the opposite applies to low plasticity. Resilience and vulnerability are not univocally associated to high or low plasticity. Consequently, individuals should undergo different preventive and therapeutic strategies according to their plasticity levels and living conditions. Here, an operationalization of plasticity relying on network theory is proposed: the strength of the connection among the network elements defining the individual, such as its symptoms, is a measure of plasticity. This theoretical framework represents a promising tool to investigate research questions related to changes in neural structure and activity and in behavior, and to improve therapeutic strategies for psychiatric disorders, such as major depression. Graphical Abstract: ga1 Highlights: Plasticity refers to the capacity to modify brain and behavior. High plasticity leads to a greater susceptibility to change brain and behavior according to context. Plasticity is not beneficial per se but its value must be estimated according to the context. Resilience arises from the interaction between plasticity levels and the context. Network theory allows for an operationalization and formal measure of plasticity.